Histone methyltransferase ASH1L primes metastases and metabolic reprogramming of macrophages in the bone niche - Chenling Meng; Kevin Lin; Wei Shi; Hongqi Teng; Xinhai Wan; Anna DeBruine; Yin Wang; Xin Liang; Javier Leo; Feiyu Chen; Qianlin Gu; Jie Zhang; et al. (Nature Communications)
Abstract Bone metastasis is a major cause of cancer death; however, the epigenetic determinants driving this process remain elusive. Here, we report that histone methyltransferase ASH1L is genetically amplified and is required for bone metastasis in men with prostate cancer. ASH1L rewires histone methylations and cooperates with HIF-1α to induce pro-metastatic transcriptome in invading cancer cells, resulting in monocyte differentiation into lipid-associated macrophage (LA-TAM) and enhancing their pro-tumoral phenotype in the metastatic bone niche. We identified IGF-2 as a direct target of ASH1L/HIF-1α and mediates LA-TAMs’ differentiation and phenotypic changes by reprogramming oxidative phosphorylation. Pharmacologic inhibition of the ASH1L-HIF-1α-macrophages axis elicits robust anti-metastasis responses in preclinical models. Our study demonstrates epigenetic alterations in cancer cells reprogram metabolism and features of myeloid components, facilitating metastatic outgrowth. It establishes ASH1L as an epigenetic driver priming metastasis and macrophage plasticity in the bone niche, providing a bona fide therapeutic target in metastatic malignancies.